The adoption of care robots in home care—A survey on the attitudes of Finnish home care personnel. Issue 9 (May 2018) - Rantanen, Teemu; Lehto, Paula; Vuorinen, Pertti; Coco, Kirsi
Abstract : Aims and objectives: This article examines the attitudes of Finnish home care registered nurses, licensed vocational nurses and other health and social care personnel towards the introduction and use of care robots in home care. Background: The significance of care robotics has been highlighted in recent years. However, personnel‐related social psychological barriers to the introduction of care robots have been given very little study. Design: Cross‐sectional study conducted by questionnaire. The theoretical framework of the study is based on Ajzen's theory of planned behaviour and the research discussion about attitudes towards robots. Methods: The research data were collected in five municipalities in different parts of Finland in 2016, and the questionnaire was answered by a total of 200 home care workers. The research data were analysed using exploratory factor analysis, Pearson product–moment correlation, one‐way analysis of variance and linear regression analysis. Results: The results are consistent with Ajzen's theory and previous studies on the acceptance of information systems in health care. Personnel behavioural intentions related to the introduction of robot applications in home care are influenced by their personal appreciation of the usefulness of robots, the expectations of their colleagues and supervisors, as well as by their own perceptions of their capacity to learn to use care robots. In particular, personnel emphasised the value of care robots in providing reminders and guidance, as well as promoting the safety of the older people. Conclusions: The study shows that an intimate human–robot relationship can pose a challenge from the perspective of the acceptance of care robots. Relevance to clinical practice: From the perspective of the introduction of care robots in home care, personnel training and the construction of a positive working atmosphere play a key role. In addition, the introduction of robots requires further consideration of a number of ethical issues.